The Influence of Tourist Experience and Tourist Satisfaction on Revisit Intention to Aling-Aling Waterfall - I Putu Ari Yogiantara; Komang Endrawan Sumadi Putra (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study aims to examine the influence of tourist experience and tourist satisfaction on revisit intention to the Aling-Aling Waterfall tourist destination in Buleleng Regency. The background of this research is based on the phenomenon of fluctuating tourist visits, which indicates that natural attractions alone are not sufficient to ensure the sustainability of visits. This research employs a quantitative approach with an associative design. The population consists of tourists visiting Aling-Aling Waterfall during the 2022–2024 period, with a total sample of 100 respondents selected using purposive sampling. The research instrument was developed using a five-point Likert scale with indicators of tourist experience (education, aesthetics, entertainment, escapism), tourist satisfaction (nature, culture, overall service), and revisit intention. Data were analyzed using multiple linear regression with SPSS. The results show that both tourist experience and tourist satisfaction have a positive and significant effect on revisit intention.These findings highlight the importance of memorable experiences and tourist satisfaction in fostering loyalty and supporting the sustainability of nature-based tourism in Buleleng.